Data from: Maternal nesting behaviour in city dragons: a species with temperature-dependent sex determination - Kent, Nicola; Cristescu, Romane H.; Piza-Roca, Carme; Littleford-Colquhoun, Bethan L.; Strickland, Kasha; Frère, Céline H. (Dryad, 2019)
Urban environments present some of the greatest challenges to species
survival. This is particularly true for species that exhibit thermally
sensitive traits, such as temperature-dependent sex determination (TSD).
This is because urban environments not only present species with entirely
novel ecosystems, but species will also experience increased temperatures.
These temperature increases may result not only in offspring mortality,
but also skewed population sex ratios. To persist in cities, urban
dwellers with TSD will therefore need to adjust the temperature of the
nesting environment, either through phenotypic plasticity or rapid
evolution through natural selection. Here, we investigate the nesting
ecology of a long-lived, urban dwelling reptile, the eastern water dragon
(Intellagama lesueurii), to understand how a TSD species may respond to
urban environments. Based on data collected from 72 nests over 2 nesting
seasons, we show that city dragons not only dug significantly deeper nests
than previously observed across their natural riparian habitat, but also
nested in novel substrates. Furthermore, we observed a behaviour not
previously described in this species, where mothers travel outside of
their core home range to nest. This excursion behaviour potentially
represents a greater maternal investment and is linked to the selection of
specific microhabitats.
Clutch sizeNesting data from 2016-2017 from Eastern Water Dragons at Roma
Street Parklands. File includes Nest (1 presence), name of the nest,
latitude, longitude, slope measured in degrees, canopy cover, soil
compactness (kg/cm), soil type, top soil type, clutch size, mother of the
clutch (if known), and season nest was found.Enviro_data_masterFile
includes environmental variables for Eastern Water Dragon nests and
randomly sampled points at Roma Street Parklands. Data is displayed as
follows: Nest (1 = presence, 0 = absence), ID of nest or random point,
latitude, longitude, compass aspect of the point or nest sampled, slope in
degrees, canopy cover, soil compactness (kg/cm), soil type of the nest,
top soil, mother of the nest (if known), and season the nest was
collected.Maternal_excursionsFile includes data for maternal excursions
for Eastern Water Dragons at Roma Street Parklands. Data is as follows: ID
of nest, maternal ID, total area of mothers 95% KUD (home range),
proportion of sand in that home range, proportion of loam in that home
range, number of points sampled in home range, number of loam points
sampled in home range, number of sand points sampled in home range, nest
soil type, excursion behaviour of mother (1 = nesting excursion, 0 = no
excursion), length of the excursion, log transformed length of excursion,
and log10 transformed length.nest depthIncludes nest depth measurements
for Eastern Water Dragons at Roma street Parklands over 2016-2017 nesting
seasons.
Keywords: 2016-2017; urbanisation; Urban Dweller; temperature-dependent sex determination; Intellagama lesueurii; Eastern Water Dragon